Conservation of Outer Membrane Protein E among Strains of Moraxella catarrhalis - Murphy, Timothy F. (American Society for Microbiology, 2001)
Outer membrane protein E (OMP E) is a 50-kDa protein of Moraxella catarrhalis which has several features that suggest that the protein may be an effective vaccine antigen. To assess the conservation of OMP E among strains of M. catarrhalis, 22 isolates were studied with eight monoclonal antibodies which recognize epitopes on different regions of the protein. Eighteen of 22 strains were reactive with all eight antibodies. The sequences of ompE from 16 strains of M. catarrhalis were determined, including the 4 strains which were nonreactive with selected monoclonal antibodies. Analysis of sequences indicate a high degree of conservation among strains, with sequence differences clustered in limited regions of the gene. To assess the stability of ompE during colonization of the human respiratory tract, the sequences of ompE of isolates collected from patients colonized with the same strain for 3 to 9 months were determined. The sequences remained unchanged. These results indicate that OMP E is highly conserved among strains of M. catarrhalis, and preliminary studies indicate that the gene which encodes OMP E remains stable during colonization of the human respiratory tract.